Information Technologies and Mathematical Modelling - Queueing Theory and Applications : 14th International Scientific Conference, ITMM 2015, named after A. F. Terpugov, Anzhero-Sudzhensk, Russia, November 18-22, 2015, Proceedings - Dudin, Alexander; Nazarov, Anatoly; Yakupov, Rafael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings fo the 14th International Scientific Conference on Information Technologies and Mathematical Modeling, named after A. F. Terpugov, ITMM 2015, held in Anzhero-Sudzhensk, Russia, in November 2015. The 35 full papers included in this volume were carefully reviewed and selected from 89 submissions. They are devoted to new results in the queueing theory and its applications, addressing specialists in probability theory, random processes, mathematical modeling as well as engineers dealing with logical and technical design and operational management of telecommunication and computer networks.
Queuing theory and its applications -- Probabilistic theory -- Random processes.-Mathematical modeling -- Logical and technical design -- Operational management of telecommunication and computer networks.
Keywords: Computer science; Computer system performance; Distribution (Probability theory; Computer Communication Networks; Computer simulation; Probability and Statistics in Computer Science; System Performance and Evaluation; Probability Theory and Stochastic Processes; Computer Communication Networks; Simulation and Modeling